Reflective practice for teachers - Sellars, Maura (London, United Kingdom : Sage Publications, 2014)
A guide to reflective practice specifically for trainee teachers, helping students to improve their own teaching practice through critical reflection across all areas of teaching.
Reflective Practice -- Teaching as Professional Practice -- Education in the Twenty-First Century -- The Learning Process -- Teaching for Learning -- Theories on the Nature of Intelligence -- Emotional Intelligence -- The Importance of Positive Thinking -- Self Directed Learning -- Understanding Student Diversity -- Skills and Strategies for Differentiation -- Beginning Your Teaching Career.
Includes bibliographical references and index.
Keywords: REFLECTIVE TEACHING